Risk-Reducing Bilateral Salpingo-Oophorectomy for Ovarian Cancer: A Review and Clinical Guide for Hereditary Predisposition Genes. Issue 3 (March 2022) - Liu, Ying L.; Breen, Kelsey; Catchings, Amanda; Ranganathan, Megha; Latham, Alicia; Goldfrank, Deborah J.; Grisham, Rachel N.; Long Roche, Kara; Frey, Melissa K.; Chi, Dennis S.; Abu-Rustum, Nadeem; Aghajanian, Carol; et al.
Abstract : Pathogenic germline variants underlie up to 20% of ovarian cancer (OC) and are associated with varying degrees of risk for OC. For mutations in high-penetrance genes such as BRCA1 / 2, the role of risk-reducing bilateral salpingo-oophorectomy (RRSO) in cancer prevention is well-established and improves mortality. However, in moderate-penetrance genes where the degree of risk for OC is less precisely defined, the role of RRSO is more controversial. Although national guidelines have evolved to incorporate gene-specific recommendations, studies demonstrate significant variations in practice. Given this, our multidisciplinary group has reviewed the available literature on risk estimates for genes associated with OC, incorporated levels of evidence, and set thresholds for consideration of RRSO. We found that the benefit of RRSO is well-established for pathogenic variants in BRCA1 /2 as well as BRIP1 and RAD51C / D where the risk of OC is elevated beyond our threshold for RRSO. In PALB2, RRSO is particularly controversial as newer studies consistently demonstrate an increased risk of OC that is dependent on family history, making uniform recommendations challenging. Additionally, new guidelines for Lynch syndrome provide gene-specific risks, questioning the role of RRSO, and even hysterectomy, for MSH6 and PMS2 mutation carriers. Given these uncertainties, shared decision making should be used around RRSO with discussion of individual risk factors, family history, and adverse effects of surgery and premature menopause. Herein, we provide a clinical guide and counseling points.